Step-by-step explanation:
by having two equations that have the same point, you can set the two equations equal to each other
y = 12x + 3, y = x + 1
12x + 3 = x + 1
11x = -2
x = -2/11
when you find the the x value, plug it back into either one of the equations
y = x + 1
y = (-2/11) + 1
y = 11/11 - 2/11
y = 9/11
the point (solution):
(-2/11, 9/11)
Answer:
Check explanation
Step-by-step explanation:
![\frac{3(x+2)}{3(x+3)(x+3)}*\frac{(x+3)(x-4)}{(x+2)(x-2)}](https://tex.z-dn.net/?f=%5Cfrac%7B3%28x%2B2%29%7D%7B3%28x%2B3%29%28x%2B3%29%7D%2A%5Cfrac%7B%28x%2B3%29%28x-4%29%7D%7B%28x%2B2%29%28x-2%29%7D)
Answer:
m<1=120
Step-by-step explanation:
A linear pair adds up to 180 degrees.
So <1+<2=180
Let <2=X, that would make <1=2X because <1 is 2 times more.
So substitute that into the equation.
2x+x=180.
Combine like terms and get 3x=180
Divide both sides by 3 and get x=60.
Substitute that into <1 and get <1=120
Answer:
Step-by-step explanation:
where is the question?